BaSb(H2PO2)3Cl2: An excellent UV nonlinear optical hypophosphite exhibiting strong second-harmonic generation response. (November 2022) - Long, Y.; Dong, X.; Huang, L.; Zeng, H.; Lin, Z.; Zhou, L.; Zou, G.
Abstract: Non π-conjugated tetrahedral groups have emerged as potential basic modules for developing ultraviolet (UV) nonlinear optical materials. However, their intrinsic weak hyperpolarizability and small polarizability anisotropy severely restrict the performance of the designed material. Herein, the first antimony hypophosphite, BaSb(H2 PO2 )3 Cl2, was successfully synthesized via rational design, which exhibits superior nonlinear optical properties including strong second harmonic generation response, appropriate birefringence and wide transmittance, indicating it is a potential UV nonlinear optical material. Remarkably, the title compound exhibits the largest nonlinear optical coefficient (5 × KDP) among all reported antimony-based oxyacid compounds. Detailed theoretical calculations confirmed that its excellent nonlinear optical properties are primarily derived from the ordered [Sb(H2 PO2 )3 Cl2 ] 2- anionic clusters composed of [H2 PO2 ] - pseudo-tetrahedra and [SbO3 Cl2 ] 5- distorted polyhedra. This work would extend UV nonlinear optical material system to hypophosphites and lead the further inquiry of new structure-driven functional materials. Graphical abstract: Image 1 Highlights: The hypophosphite was introduced into the antimony-system for the first time by a simple solvent evaporation method. The BaSb(H2 PO2 )3 Cl2 exhibits large SHG (5.0 × KDP), moderate birefringence (0.09@546 nm), and wide bandgap (4.2 eV). The proposed cation-anion synergetic interaction strategy provides new ideas for further design of optical materials.